A new image scrambling technique using block rotation algorithm based on Rubik’s cube - Abugharsa, Ahmed Bashir; Hasan Basari, Abd Samad; Almangush, Hamida (AENSI Publisher, 2013)
Background:. Image scrambling is a useful approach to secure the image data by scrambling the image into an unintelligible format. The relationship among the adjacent pixels of image is very high. Also, Most image scrambling algorithms apply one iteration level scrambling that cause a high possibility of occurs the weakness of visual leakage on the image scrambling algorithm which can be reflected by the corresponding scrambled image. Objectives: the objective of this paper is to develop a new efficient image scrambling algorithm by using the Rotation technique in order to break the relationship among image elements (pixels). Thus, to develop an efficient scheme to generate non fixed iteration in the image scrambling algorithm in order to eliminate the problem of visual leakage. Results: The results show that the correlation between image elements has been significantly decreased using the proposed technique, and higher entropy has been achieved. Furthermore, implies a high similarity and a good quality of the retrieved image compared to the original image. Conclusion: This paper proposes a new scramble algorithm which can be produced by a series of rotation the rows and the columns into six sub-image that attached to the faces of the virtual Rubik’s cube. The first part of the algorithm aims to build a rotation table using hash function within scramble phase and descramble phase to generate a scrambled (rotated) image and the retrieved image. The second part of the algorithm uses the rotation table resulted from the first part of the algorithm to generate newly rotated image (Scrambled) in which the rows and the columns of the original image are rotated after divide it to six sub-image and attach then to the faces of the virtual Rubik’s cube . This makes the scrambled images difficult to decode thus providing a high level of security protection for the images. The algorithm can be applied in the real-time applications since it is a straightforward process and easily implemented.